Arrangement of Coastal Slums in Pagurawan Village, Batu Bara Regency - Gunawan Sinaga; Cut Nuraini; Abdi Sugiarto (CV. Doki Course and Training, 2026)
This study examines the existing conditions of a coastal informal settlement in Pagurawan, Batu Bara Regency, with emphasis on housing quality, basic infrastructure, and environmental sanitation, and formulates an appropriate, context-sensitive upgrading strategy for a fishermen community. A qualitative case-study design was used, combining field observations, document review, and community/stakeholder inputs. The findings indicate multiple, interacting drivers of deprivation: limited access to safe water and sanitation, inadequate drainage and solid waste services, high exposure to coastal hazards (tidal flooding and abrasion), insecure tenure, and constrained household livelihoods. Building on recent evidence from community-based sanitation and slum-upgrading practices in Batu Bara and North Sumatra, the paper proposes a staged upgrading framework: rapid WASH improvements and waste management, climate-adaptive access infrastructure, incremental tenure arrangements, ecosystem-based coastal protection, and livelihood strengthening through cooperative-based value addition. The proposed strategy highlights the need for collaborative governance that aligns municipal programs, community organizations, and private/CSR support to ensure both technical suitability and long-term operation.